Ruminants (Giraffidae and Bovidae) from Kanapoi. Issue 140 (March 2020) - Geraads, Denis; Bobe, René
Abstract: We update here our recent revision of the Kanapoi ruminants and describe recently collected material. We now regard the occurrence of reduncins as doubtful, we revise the identification of a large raphicerin as being more probably Gazella, and we add Gazella cf. janenschi and the Cephalophini to the faunal list. New material of Tragelaphus kyaloi suggests that this species held its head unlike other tragelaphins, and was not an exclusive dedicated browser, but Kanapoi pre-dates the Pliocene change of Sivatherium, Aepyceros, Alcelaphini, and even Tragelaphini toward more grazing diets. Kanapoi shares several ruminant taxa with sites in Ethiopia and Tanzania, attesting to latitudinal exchanges.